Governance efficacy as a hybrid good: Integrating AI, foresight, and digital nudging for smart growth - Elias G. Carayannis; Nikos-Rigert Zota (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
This paper advances a conceptual reframing of governance efficacy as a hybrid public-private good, co-produced through the convergence of Artificial Intelligence (AI), Strategic Foresight, and Digital Nudging. It argues that in the digital era, governance efficacy transcends traditional notions of bureaucratic performance to become a systemic capacity grounded in anticipation, adaptability, and ethical legitimacy. Through an integrated framework, the paper elucidates how AI enhances cognitive intelligence and responsiveness, foresight institutionalizes long-term preparedness and resilience, and digital nudging aligns behavioral engagement with collective values. Together, these enablers form a triadic architecture of "intelligent governance" that links technological capability with public purpose. The analysis applies the TP³ (Theories-Policies- Practices-Politics) lens to trace how hybrid governance operates across institutional layers and sectoral contexts, from public administrations and corporate foresight systems to cross-sectoral partnerships. Comparative illustrations demonstrate that hybrid governance efficacy is not merely an administrative function but an emergent outcome of co-evolution between human and technological intelligence. The study contributes to governance theory by redefining efficacy as a dynamic, ethically grounded, and anticipatory capacity that underpins smart growth, resilience, and sustainable societal transformation.
Keywords: H83; O33; D78; L86; Z18; 330; Hybrid Governance; Governance Efficacy; Artificial Intelligence (AI); Strategic Foresight; Digital Nudging; Smart Growth; Adaptive and Anticipatory Governance